Rancang Bangun Pembangkit Listrik Tenaga Bayu dengan Sistem Monitoring Pengisian Battery Berbasis Internet of Things (IoT) - Ahmad Alif Farhan; Diana Alia; Hadi Setiawan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Extreme climate change in Indonesia, caused by air pollution from the use of fossil energy, has encouraged the development of renewable energy technology, including Wind Power Plants (PLTB). This technology is increasingly important for providing clean energy, especially in the maritime industry. The aim of this applied scientific work is to provide a battery charging solution when the emergency battery charger charging system on commercial ships experiences problems. To make it easier to monitor the power produced by wind power plants and also battery capacity via a smartphone application in real time. The method used in this applied scientific research research is experimental. The results of calculating the average power during testing at night show an average power of 10.22 Watt/min and an average current of 0.78 A. So it can be concluded that battery charging takes 11.53 hours. Meanwhile, the results of calculating the average power during testing during the day show an average power of 13.41 Watt/min and an average current of 1.02 A. So it can be concluded that charging the battery lasts for 8.82 hours. From the two data obtained, it can be concluded that charging is optimal during the day because the efficient charging time is 8.82 hours.